Pengucapan Salam Lintas Agama Menurut Ulama Jawa Timur - Athifatul Wafirah; Miftakhul Nur Arista; M. Sholahuddin; M. Kosim; Nur Lailatul Musyafa’ah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
This article discusses the Interfaith Greeting Prayer according to East Javanese scholars. What is meant by the ulama of East Java in this article are the ulama of the MUI and Muhammadiyah of East Java. The fatwa of the East Java MUI explains that saying interfaith greetings is haram based on Surah al-Baqoroh verse 42 and Surat al-Kafirun verse 6. While one Muhammadiyah figure thinks that interfaith greetings are allowed, if they are meant only as a greeting in an activity or speech state and does not contain the aim of grazing the creed, because it is part of the min an-nas hablun. However, if the saying of greetings across religions is a lot of harm, then the law is haram.